Analysis of The Effectiveness and Efficiency of Government Policies for Valuing Veteran Rights - Amelia da costa; Alexandre de Sousa Guterres; Mateus Xavier da Costa Cabral (CV. Ulil Albab Corp, 2025)
The aim of this research is to study, analyze and describe in more depth the effectiveness and efficiency of government politics to appreciate veterans' rights. Thus the author uses theoretical references in the form of analysis theory (grand theory) according to Ling Gie (1989:26) who says that analysis is the whole series. a change of mind that examines something in depth, especially studying parts and a whole to find out the characteristics of each, their relationship to each other and their role in the rounded whole. And it can also be complemented by supporting theories such as: effectiveness theory, efficiency, political theory, definition of appreciation, rights theory, and definition of veteran. In this research, the researcher used descriptive qualitative methods to describe government politics to appreciate veterans' rights, especially in Manufahi district. The research information in question is the Manufahi Veterans Commission, veterans who have received their rights and also veterans who feel marginalized from their rights as fighters, all of whom consist of of 8 people. Data collection techniques in this research are observation, documentation interviews and interactive model data analysis techniques according to Miles & Huberman (2017:247) to expedite the existing research process. The conclusion of all research results regarding the analysis of the effectiveness and efficiency of government politics in appreciating veterans' rights. The government's policy of appreciating veterans' rights has not been effective and efficient. Veterans' problems will become more complex for the government to resolve. The political and discriminatory problems resulting from the implementation of pension and renovation policies further increase the dissatisfaction of veterans. Veterans' problems will not be resolved if there are still veterans who feel marginalized. from government politics. Party system practices and favoritism in the process of collecting veteran data become obstacles for the government to solve veterans' problems if the process remains non-transparent, the influence of political parties and the family system becomes a barrier to finding solutions to veterans' problems correctly and definitively. The problem will become complicated in the future, because both individuals and groups of veterans feel dissatisfied with the politics implemented by the government.